Euthyroid Sick Syndrome in Patients With COVID-19 - Zou, Runmei; Wu, Chenfang; Zhang, Siye; Wang, Guyi; Zhang, Quan; Yu, Bo; Wu, Ying; Dong, Haiyun; Wu, Guobao; Wu, Shangjie; Zhong, Yanjun (Frontiers in Endocrinology, 2020)
Background Coronavirus disease 2019 (COVID-19) has been shown to affect almost every organ throughout the body. However, it is not clear whether the thyroid gland is impaired in COVID-19 patients. Euthyroid sick syndrome (ESS) is usually associated with the disease severity and deterioration prognosis in critical illness. In this study, the thyroid function of COVID-19 patients was assessed and factors associated with outcomes were analyzed to determine the potential predictive value of ESS. Methods Clinical and laboratory data of COVID-19 patients with or without ESS in Changsha, China, were collected and analyzed on admission. Kaplan-Meier curve and cox regression model were utilized to determine the correlation between ESS and the endpoints. Subsequently, a receiver operating characteristic (ROC) curve was plotted to evaluate the predictive performances of FT3 and C reactive protein (CRP) in the disease severity. Results 41 (27.52%) cases of COVID-19 patients diagnosed with ESS. ESS patients had higher proportions of fever, shortness of breath, hypertension, diabetes, and severe events than those of non-ESS patients. The levels of erythrocyte sedimentation rate and C-reactive protein, and the positive rate of procalcitonin were significantly higher, whereas the lymphocyte count was apparently lower in ESS patients than in non-ESS patients. The regression analysis showed that ESS was significantly associated with the disease severity of COVID-19 (HR = 2.515, 95% CI: 1.050-6.026, P = 0.039). The areas under the curve (AUCs) for predicting the severe disease were [0.809 (95% CI 0.727-0.892), P < 0.001] and [0.792 (95% CI 0.689-0.895), P < 0.001] for FT3 and CRP, respectively. Conclusion ESS was significantly associated with the disease severity and inflammatory parameters in COVID-19 patients.